STRATEGI TEKNIS PENANGANAN LALU LINTAS (STUDI KASUS KAWASAN PELABUHAN MENGKAPAN) - Frans Deddy Arisandy; Rizki Ramadhan Husaini (Racic : Rab Construction Research, 2024)
This research focuses on the port area of Mengkapan in Siak Regency, specifically on the Sumatra Transcontinental Highway. During holidays, the Vehicle/Capacity (V/C) Ratio on this road reaches 0.631. This is attributed to the constraint of vehicle parking on the road, hindering the entry and exit of vehicles from the port and causing congestion during peak hours between 13:00 and 14:30 WIB. The road speed decreases to 30 km/h, resulting in queues and congestion reaching the Sumatra Transcontinental Highway, the main route to the Mengkapan port area. The objective of this study is to evaluate the effectiveness and efficiency of traffic services on the Sumatra Transcontinental Highway and the port access road. Using VISSIM software and based on calculations from the Indonesian Road Capacity Manual (MKJI), an analysis is conducted on intersection performance, road speed, vehicle delay, and traffic volume in the Mengkapan port area. The findings of this analysis serve as a basis for recommending traffic engineering management strategies to enhance services on 2the Sumatra Transcontinental Highway and port access roads. The implications of these findings are used as a reference for the government in formulating policies to improve the capacity and performance of the transportation system in the area.